RANCANG BANGUN PERAHU TANPA AWAK TENAGA SURYA (PETATES) Auto Feeder - Prihantoro, Topan; Asha, Muhammad Toasin; Pratama, Wahyu Wira; Daryono, Daryono; Setiawan, Agus; Sofiana, Evi; Ali, Muhammad; Riyanti, Rika; Reski, Indah Anjar (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
Feeding fish in pond-based aquaculture involves the hand distribution of food by individuals around the pond's perimeter. Farmers utilize boats to achieve extensive food delivery. Technological advancements have facilitated the creation of self-feeder or dement-feeder statistical techniques. This device functions autonomously to provide feed at regular intervals and has a predetermined coverage area at its designated position on the periphery of ponds. Due to its peripheral location, the technology deployment system has limited capacity to distribute feed across the entire pond area, making it less effective for use in big ponds. Hence, it is imperative to develop a solar-powered unmanned boat (Petates) equipped with an Auto Feeder system to regulate the feeding process in shrimp and fish farming. This study aims to develop a solar-powered unmanned boat design for fish and shrimp farming that can efficiently distribute feed across the pond. Additionally, the research aims to assess the impact of feeding machines on the conversion of feed by fish and shrimp. The research results show that the maximum floating weight of the boat is 48.7 kg using two solar-powered electromotor-driven buoys. The boat has a maximum speed acceleration of 2.4 m/s, achieved through a well-balanced and efficient bow acceleration. Experiments were conducted using two distinct feed types: type 781-2 with a diameter ranging from 2.3 to 3 mm, and type 781-3 with a diameter ranging from 3.2 to 4 mm. The throwing distance for the feed is between 8 and 10 meters, and between 7 and 8 meters. The feed spreading rate for each minute is 950 grams and 1,080 grams, with a feed capacity of 7 kilograms and 6 kilograms respectively.